The Coordinated Upregulated Expression of Genes Involved in MEP, Chlorophyll, Carotenoid and Tocopherol Pathways, Mirrored the Corresponding Metabolite Contents in Rice Leaves during De-Etiolation - Jin, Xin (Plants (Basel), 2021)
Light is an essential regulator of many developmental processes in higher plants. We investigated the effect of 4-hydroxy-3-methylbut-2-enyl diphosphate reductase 1/2 genes (OsHDR1/2) and isopentenyl diphosphate isomerase 1/2 genes (OsIPPI1/2) on the biosynthesis of chlorophylls, carotenoids, and phytosterols in 14-day-old etiolated rice (Oyza sativa L.) leaves during de-etiolation. However, little is known about the effect of isoprenoid biosynthesis genes on the corresponding metabolites during the de-etiolation of etiolated rice leaves. The results showed that the levels of α-tocopherol were significantly increased in de-etiolated rice leaves. Similar to 1-deoxy-D-xylulose-5-phosphate synthase 3 gene (OsDXS3), both OsDXS1 and OsDXS2 genes encode functional 1-deoxy-D-xylulose-5-phosphate synthase (DXS) activities. Their expression patterns and the synthesis of chlorophyll, carotenoid, and tocopherol metabolites suggested that OsDXS1 is responsible for the biosynthesis of plastidial isoprenoids in de-etiolated rice leaves. The expression analysis of isoprenoid biosynthesis genes revealed that the coordinated expression of the MEP (2-C-methyl-D-erythritol 4-phosphate) pathway, chlorophyll, carotenoid, and tocopherol pathway genes mirrored the changes in the levels of the corresponding metabolites during de-etiolation. The underpinning mechanistic basis of coordinated light-upregulated gene expression was elucidated during the de-etiolation process, specifically the role of light-responsive cis-regulatory motifs in the promoter region of these genes. In silico promoter analysis showed that the light-responsive cis-regulatory elements presented in all the promoter regions of each light-upregulated gene, providing an important link between observed phenotype during de-etiolation and the molecular machinery controlling expression of these genes.